The Effect of Dextromethorphan Premedication on Cough and Patient Tolerance During Flexible Bronchoscopy: A Randomized, Double-blind, Placebo-controlled Trial. Issue 4 (October 2017) - Amini, Shahideh; Peiman, Soheil; Khatuni, Mahdi; Ghalamkari, Marziyeh; Rahimi, Besharat
Abstract : Background: Patients undergoing bronchoscopy can experience problems such as anxiety and cough, requiring various doses of sedatives and analgesics. The purposes of this study were to investigate the effect of premedication with dextromethorphan on patients' cough and anxiety, and the use of analgesics/sedatives during flexible bronchoscopy (FB). Methods: A randomized, double-blind, placebo-controlled, prospective study was performed to assess the effect of dextromethorphan premedication on patients who underwent diagnostic bronchoscopy. Seventy patients included in this study were randomly allocated into 2 groups: group A consisted of 35 patients who received dextromethorphan before FB; and group B consisted of 35 patients who received a placebo. A questionnaire was given to the patients and bronchoscopist about perception of cough, anxiety, and discomfort. The amount of sedative medication and lidocaine use during the procedure and the procedure time were recorded. Results: The group that was premedicated with dextromethorphan had lower complaint scores, significantly less coughing, significantly less stress assessed by the patient and the physician evaluation, shorter total procedure time, and fewer midazolam requirements during FB ( P -value <0.05). Conclusion: Considering its safety profile, dextromethorphan premedication is an effective approach to facilitate the performance of FB for the physician, and could improve patient comfort.